Organizational Rules and Cognitive Uncertainty Among Public Professionals: A Daily Diary Study. (December 2021) - Bernards, Bernard; van der Voet, Joris; van der Pas, Suzan; Groeneveld, Sandra
Although public management and human resource management research has extensively investigated the motivational effects of organizational rules, the original utility of organizational rules—uncertainty reduction—has remained overlooked. This study takes a cognitive perspective by examining how organizational rules relate to uncertainty experiences of public professionals. In this study, we provide a dynamic perspective on the relationship between organizational rules and uncertainty through a 2-week daily online diary study among 65 public professionals in the Netherlands. The results indicate that the amount and consistency of rules are related to professionals' daily uncertainty experiences. Moreover, within-person experiences of rules and uncertainty are highly variable over time. We argue that a cognitive perspective of uncertainty reduction can broaden our understanding of the consequences of organizational rules in managing people, and that the dynamic nature of organizational rule experiences cannot be a mere footnote in future public administration and human resource management research.